1997
DOI: 10.1111/j.1432-1033.1997.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Carbamoyltransferase from the Extreme Thermophile Thermus Thermophilus Analysis of the Gene and Characterisation of the Protein

Abstract: The ornithine carbamoyltransferase (OTC) gene from Thermus thermophilus was cloned from a ).-ZAP genomic library. An ORF of 903 bp was found coding for a protein of M , 33200. The coding region has a very high overall G + C content of 68.0%. 7: thermophilus OTC displays 38-48% amino acid identity with other OTC, the most closely related proteins being OTC from the archaeon Pyrococcus jiiriosus and from Bacillus subtilis. The enzyme was expressed in Escherichia coli and purified to homogeneity using a thermosho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The optimal pHs for the reaction at 20°C were found to be between 9.0 and 10.0 (data not shown), whereas E. coli and T. thermophilus OTCases display broad optimal activity at about pH 8.0 (31,45). As expected for an anabolic OTCase (9), the reaction catalyzed by OTCase Mab displayed no allosteric kinetics.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The optimal pHs for the reaction at 20°C were found to be between 9.0 and 10.0 (data not shown), whereas E. coli and T. thermophilus OTCases display broad optimal activity at about pH 8.0 (31,45). As expected for an anabolic OTCase (9), the reaction catalyzed by OTCase Mab displayed no allosteric kinetics.…”
Section: Resultsmentioning
confidence: 87%
“…Cold-active enzymes are frequently thermolabile, a fact which is understandable, since they have to be flexible enough to be active at a low energy cost (14). OTCase Mab is indeed considerably less resistant to thermal inactivation (Table 3) and has a weaker conformational stability (Table 4) than its E. coli or thermophilic counterparts (32,33,45). Psychrophilic enzymes counteract the inhibitory effect of low temperatures on activity by reducing the temperature dependence of the reaction rate (low activation enthalpy).…”
Section: Discussionmentioning
confidence: 99%
“…One may argue that the product of coregulated ORFs could stabilize enzymes encoded by the same polycystronic mRNA (13). However, in Thermus, the argF and argJ gene products appear intrinsically stable (1,27). Another possibility would be that the unknown ORF product is involved in the formation of multienzyme complexes channeling arginine metabolic precursors (17,32).…”
mentioning
confidence: 97%
“…The intensity was strongly reduced with RNA extracted from cells grown in the presence of arginine. Previous experiments already indicated that arginine represses OTCase synthesis in Thermus (27,31). The region thus appears to contain four consecutive transcription units: ORF6, ORF7, ORF8, argF; ORF1, argC, argJ; ORF4; and ORF5.…”
mentioning
confidence: 99%
See 1 more Smart Citation